Post-feeding carbohydrate and ketone bodies metabolism in brain and liver of Atlantic salmon. (Revista Española de Fisiología, 1996)
A study of several pathways of carbohydrate and ketone bodies metabolism was carried out in Atlantic salmon (Salmo salar) to assess the basal metabolism of the brain, and the possible existence of post-feeding changes in brain and liver metabolism. The main results obtained in brain of Atlantic salmon indicate a use of exogenous glucose as a main fuel source since important hexokinase activities were noticed, and brain glycogen levels were usually very low. Several post-feeding changes were observed in brain including an apparent decrease in glycolytic potential, as well as a decreased use of ketone bodies. In contrast, no major post-feeding changes were detected in liver metabolism. A role for ketone bodies as a metabolic fuel in brain of Atlantic salmon is supported by both the high levels of acetoacetate found in brain, and the presence of an active beta-hydroxybutyrate dehydrogenase.